(untitled) (Eurasian Journal of Ecology, 2016)
Bone remodeling is a process orchestrated by two types of cells: osteoblasts and osteoclasts. Induced osteoclastic activity and reduction of osteoblasts result in progressive bone loss, which could be amended by introduction of mesenchymal stem cells (MSCs). Bone targeted MSCs delivery can potentially increase the efficiency of cell therapy and result in alleviation of such conditions as osteoporosis and Paget Disease. We have synthesized a novel polymer which shows high affinity to bone tissue and could be used to deliver MSCs to the site of bone injury or lesion. Cytotoxic effect of the polymer was evaluated and its effect on osteogenic differentiation was shown in vitro.